PENGARUH PENYUSUTAN TERHADAP KARAKTERISTIK PENGERINGAN TEMU PUTIH - Lamhot P. Manalu dan Armansyah H. Tambunan (Department of Agroindustrial Technology, Bogor Agricultural University, 2015)
The effects of drying conditions on shrinkage of zedoary were studied. A thin-layer dryer with machine vision 2D system and image analysis software was used. Zedoary slices were dried at temperatures of 50, 60 and 70oC (at constant RH) and relative humidities of 20%, 30% and 40% (at constant temperature). The falling drying rate data were used to calculate the effective diffusion coefficients from the Fick’s equation. Changes in area of the slice were measured every 5 minute during drying. Shrinkage showed almost linear relation with moisture content. It was found that air temperature and relative humidity had no significant effect on shrinkage. Drying took place entirely in the falling rate period. Slices dried at 70oC showed more bend than slices dried at 50 and 60oC. Effective diffusivity values by considering the shrinkage were estimated in the range of 4.74-6.19×10-9 m2/s for studied drying temperatures.Keywords: drying, shrinkage, moisture, diffusivity, image analysis, zedoary